Growing diversity of trypanosomatid parasites of flies (Diptera: Brachycera): frequent cosmopolitism and moderate host specificity - Týč, Jiří; Votýpka, Jan; Klepetková, Helena; Suláková, Hana; Jirků, Milan; Lukeš, Julius (Molecular phylogenetics and evolution, 2013)
Widely distributed, highly prevalent and speciose, trypanosomatid flagellates represent a convenient model to address topics such as host specificity, diversity and distribution of parasitic protists. Recent studies dealing with insect parasites of the class Kinetoplastea have been focused mainly on trypanosomatids from true bugs (Heteroptera), even though flies (Diptera, Brachycera) are also known as their frequent hosts. Phylogenetic position, host specificity and geographic distribution of trypanosomatids parasitizing dipteran hosts collected in nine countries on four continents (Bulgaria, Czech Republic, Ecuador, Ghana, Kenya, Madagascar, Mongolia, Papua New Guinea and Turkey) are presented. Spliced leader (SL) RNA gene repeats and small subunit (SSU) rRNA genes were PCR amplified from trypanosomatids infecting the gut of a total of forty fly specimens belonging to nine families. While SL RNA was mainly used for barcoding, SSU rRNA was utilized in phylogenetic analyses. Thirty-six different typing units (TUs) were revealed, of which 24 are described for the first time and represent potential new species. Multiple infections with several TUs are more common among brachyceran hosts than in true bugs, reaching one third of cases. When compared to trypanosomatids from heteropteran bugs, brachyceran flagellates are more host specific on the genus level. From seven previously recognized branches of monoxenous trypanosomatids, the Blastocrithidia and "jaculum" clades accommodate almost solely parasites of Heteroptera; two other clades (Herpetomonas and Angomonas) are formed primarily by flagellates found in dipteran hosts, with the most species-rich Leishmaniinae and the small Strigomonas and "collosoma" clades remaining promiscuous. Furthermore, two new clades of trypanosomatids from brachyceran flies emerged in this study. While flagellates from brachyceran hosts have moderate to higher host specificity, geographic distribution of at least some of them seems to be cosmopolitan. Moreover, the genus Angomonas, so far known only from South America, is present on other continents as well.
Keywords: protozoální DNA; Diversity; Host specificity; genetická variace; Bayes Theorem; fylogeneze; Sequence Analysis, DNA; Phylogeny; sekvenční analýza DNA; Europe; Afrika; biologická evoluce; Models, Genetic; Phylogeography; DNA, Protozoan; RNA, Ribosomal; Latinská Amerika; Trypanosomatida; Evropa; hostitelská specificita; Trypanosomatina; Animals; Africa; Biological Evolution; RNA ribozomální; zvířata; Geographic distribution; modely genetické; fylogeografie; Latin America; Bayesova věta; Leishmania; Genetic Variation; Diptera; Host Specificity